The potential for applying "Nonviolent Communication" in conservation science. Issue 11 (22nd September 2021) - Williams, Brooke A.; Simmons, B. Alexander; Ward, Michelle; Beher, Jutta; Dean, Angela J.; Nou, Tida; Kenyon, Tania M.; Davey, Madeline; Melton, Courtney B.; Stewart‐Sinclair, Phoebe J.; Hammond, Niall L.; Massingham, Emily; et al.
Abstract: The role of a conservation scientist has never been more challenging. Amidst the rapid degradation occurring across Earth's natural ecosystems and the loss of biodiversity and ecosystem services, conservation scientists must learn new and effective ways to build trust and engage with the wider community. Here, we discuss the potential utility of a particular communication technique, Nonviolent Communication (also known as Compassionate Communication or Collaborative Communication), in conservation science. Nonviolent Communication is a structured form of communication, developed in the 1960s by Dr. Marshall Rosenberg, that seeks to foster interpersonal understanding and connection through communication of judgment‐free observations, recognition of people's feelings, needs and values, and requests for specific actions to meet those needs. It has delivered positive outcomes in diverse fields such as prisoner reform, health science, and social work, and holds great promise for conservation applications. While there is no single communication strategy that resonates with all people, we argue that Nonviolent Communication could be used by conservation scientists and practitioners when communicating with colleagues, politicians, and the general public about important and sometimes contentious environmental issues.